Politeness of Students’ Short Message (SMS) to Lecturers (Pragmatic Approach) - Untung; Saasa (Penerbit STKIP PGRI Bangkalan, 2025)
In academic communication, politeness in short messages (SMS) from students to lecturers is an important aspect that reflects respect and language ethics. From a pragmatic perspective, politeness in messages is not only determined by the choice of polite words, but also by understanding the context, language function, and prevailing social norms. Based on pragmatic principles, the messages conveyed by students must pay attention to factors such as social status, the relationship between speakers and interlocutors, and the purpose of communication. For example, the use of opening greetings, polite request expressions, and polite closings shows awareness of the principle of politeness in communication. Conversely, messages that are too direct, without self-introduction, or use informal language can be perceived as lacking respect for academic norms.